Validation of the factor structure of the motivated strategies for learning questionnaire - Tran, Van Dat; Dong Le, Thi A (Institute of Advanced Engineering and Science, 2024)
In recent years, the motivated strategies for learning questionnaire (MSLQ) has been used to assess students’ motivational orientations and utilization of various learning strategies. Due to its significant effects on student outcomes such as academic performance and careers, research on the factor structure of motivated strategies for learning has received increasing attention. However, the existing literature indicates a dearth of studies focusing on the MSLQ dimensions in Vietnam. Therefore, this study aimed to ascertain the factor structure of the 31-item Student Motivation Scale (SMS), which is a subset of the larger 81-item MSLQ, in the context of Vietnam. The study utilized the Vietnamese version of the SMS to collect data from 317 high school students in Vietnam. The factorial analysis showed that the SMS has its original six-factor structure, which is made up of task value (TV), control beliefs, self-efficacy for learning and performance (SLP), test anxiety (TA), and intrinsic goal orientation (IGO). The present study recommended that school leaders and teachers should use the SMS to assess students’ motivation in the context of Vietnamese education.